(untitled) (Universal International Scientific Journal, 2026)
This article examines the role and importance of emotional intelligence in the psychological adaptation of adolescents. It analyzes the role of emotional intelligence in adolescents’ mental stability, social relationships, and adaptation to stressful situations.